Revitalization of Railway Station in Situbondo Regency - Joko Budiwiyanto; Shela Rachim (Pendhapa, 2022)
The revitalization of the railway station in Situbondo Regency is an effort to revitalize the function of the station and commercial function as a maintenance measure of a cultural heritage building in Situbondo Regency. This design aims to renew Situbondo Railway Station with facilities following the Indonesian Railway Station Service Standards. The design method includes input, synthesis/analysis, and output. This design uses the theme "Modern Meets Heritage," which is an effort to process the physical condition of building architecture as a heritage building in very rapid technological and design developments. The Interior Style used is the Art Deco interior style. Thus this design produces an interior design of a train station with hall facilities, counters, customer service, waiting rooms, executive waiting rooms, platforms, and other supporting facilities with aesthetic and good function value.